Use the identity
sec^2x = 1 + tan^2 x
- so sec x = sqrt(1 + tan^2 x) then:-
tan x + sqrt( 1 + tan^2 x) = 1
sqrt ( 1 + tan^2 x) = 1 - tan x
1 + tan^2 x = 1 + tan^2x - 2 tan x
0 = -2 tanx
tan x = 0
x = 0, π
π is an extraneous root because sec 180 = -1
So the answer is 0 degrees
Answer:
it wold be A
Step-by-step explanation:
Answer:
1. 81.0
2. I`m trying to figure that out now I will give answers when I can
Step-by-step explanation:
There is one<span> last step after getting </span>x<span> = </span>3<span>. You must check </span>x<span> = </span>3<span> in the original equation to be sure that </span>x<span> = </span>3<span> does not cause a zero denominator.</span>
Answer:
−
3
(
x
−
5
)
(
x
+
2
) hope this helps
Step-by-step explanation: